(3ebGeGJ GdMQjQjs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj , J (B516 (3g` s ((3HjJ GdebOS s)
(3ChdgG (B:s
(3bGd GdTjN GdMQjQi GdHUQi QVi Gddg Yfg (B: (3Gddge EfG fMeOc Ydi eG YdeJ ef GdHjGf , hCdgeJ ef GdJHjGf s
(3BNQgG (B:s
(3hCfG CSJZaQ Gddg eeG GhOYJgG ef GHGWjd GddZh Efg gh Cgd GdJbhi hCgd GdeZaQI hhdi GdNjQGJ ai GdOfjG hGdBNQI s
(3GdfSNI HgG MhGTs
(3ai CKfGFgG hYdi MhGTjgG JYdjbGJ hTQhM fajSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
Keywords: (3GdCOHs